Direct and indirect effects of CYTOR lncRNA regulate HIV gene expression - Kuzmina, Alona; Sadhu, Lopamudra; Hasanuzzaman, Md; Fujinaga, Koh; Schwartz, Jacob C.; Fackler, Oliver Till; Taube, Ran (PLoS pathogens, 2024)
The implementation of antiretroviral therapy (ART) has effectively restricted the transmission of Human Immunodeficiency Virus (HIV) and improved overall clinical outcomes. However, a complete cure for HIV remains out of reach, as the virus persists in a stable pool of infected cell reservoir that is resistant to therapy and thus a main barrier towards complete elimination of viral infection. While the mechanisms by which host proteins govern viral gene expression and latency are well-studied, the emerging regulatory functions of non-coding RNAs (ncRNA) in the context of T cell activation, HIV gene expression and viral latency have not yet been thoroughly explored. Here, we report the identification of the Cytoskeleton Regulator (CYTOR) long non-coding RNA (lncRNA) as an activator of HIV gene expression that is upregulated following T cell stimulation. Functional studies show that CYTOR suppresses viral latency by directly binding to the HIV promoter and associating with the cellular positive transcription elongation factor (P-TEFb) to activate viral gene expression. CYTOR also plays a global role in regulating cellular gene expression, including those involved in controlling actin dynamics. Depletion of CYTOR expression reduces cytoplasmic actin polymerization in response to T cell activation. In addition, treating HIV-infected cells with pharmacological inhibitors of actin polymerization reduces HIV gene expression. We conclude that both direct and indirect effects of CYTOR regulate HIV gene expression.
Gesehen am 25.10.2024